2020
DOI: 10.1007/s42452-020-1977-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel slow drug release bioceramic composite materials for wound dressing applications: potential of natural materials

Abstract: There is a need for friendly and affordable wound dressing materials capable of uptaking and releasing active clinical agents. Proper combinations of materials that could quickly release antibiotics at the beginning, then slow and controlled release with time would make excellent materials for wound care management. In this study, cotton handwoven fabric hydroxyapatite (derived from coralline skeletons) polylactic acid composites were developed. The developed composites were characterized in terms of their phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is reported that coral-derived hydroxyapatite particles loaded with amoxicillin drug can be used as drug delivery systems in a wound dressing. 318 Smectite and akermanite have been showed to affect different stages of wound healing by releasing bioactive ions. 204,319 Magnesium smectite led to accelerate neovascularization, collagen deposition and maturation.…”
Section: Summary and Future Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that coral-derived hydroxyapatite particles loaded with amoxicillin drug can be used as drug delivery systems in a wound dressing. 318 Smectite and akermanite have been showed to affect different stages of wound healing by releasing bioactive ions. 204,319 Magnesium smectite led to accelerate neovascularization, collagen deposition and maturation.…”
Section: Summary and Future Trendsmentioning
confidence: 99%
“…It is worth mentioning that a number of studies have also reported the use of bioactive ceramics, including hydroxyapatite and silicates such as magnesium silicate (smectite) and calcium magnesium silicate (akermanite) in wound healing research field. It is reported that coral-derived hydroxyapatite particles loaded with amoxicillin drug can be used as drug delivery systems in a wound dressing . Smectite and akermanite have been showed to affect different stages of wound healing by releasing bioactive ions. , Magnesium smectite led to accelerate neovascularization, collagen deposition and maturation .…”
Section: Summary and Future Trendsmentioning
confidence: 99%
See 1 more Smart Citation